Computational Models of Transcranial Direct Current Stimulation - Bikson, Marom; Rahman, Asif; Datta, Abhishek (Clinical EEG and neuroscience, 2012)
During transcranial direct current stimulation (tDCS), controllable dose parameters are electrode number (typically 1 anode and 1 cathode), position, size, shape, and applied electric current. Because different electrode montages result in distinct brain current flow patterns across the brain, tDCS dose parameters can be adjusted, in an application-specific manner, to target or avoid specific brain regions. Though the tDCS electrode montage often follows basic rules of thumb (increased/decreased excitability “under” the anode/cathode electrode), computational forward models of brain current flow provide more accurate insight into detailed current flow patterns and, in some cases, can even challenge simplified electrode-placement assumptions. With the increased recognized value of computational forward models in informing tDCS montage design and interpretation of results, there have been recent advances in modeling tools and a greater proliferation of publications.  In addition, the importance of customizing tDCS for potentially vulnerable populations (eg, skull defects, brain damage/stroke, and extremes of age) can be considered. Finally, computational models can be used to design new electrode montages, for example, to improve spatial targeting such as high-definition tDCS. Pending further validation and dissemination of modeling tools, computational forward models of neuromodulation will become standard tools to guide the optimization of clinical trials and electrotherapy.